ANALYSIS OF POVERTY LEVEL IN DISTRICTS/CITIES OF CENTRAL JAVA - Setyo Novianto; Heri Sudarsono (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2018)
This study aims to determine the effect of economic growth, HDI, inflation, and unemployment to poverty level in Central Java regency / city. The method of analysis used in this study is a method of panel data analysis combination between time series with cross-sectional analysis as a data processing tool using Eviews 9. The model chosen in this research is the random effect model. The result of regression model of random effect shows that economic growth, ipm, and inflation have negative effect on poverty level. While unemployment positively affect the level of poverty. For F test, the variable of economic growth, HDI, inflation, and unemployment together (simultaneously) have an effect on poverty level.